2015
DOI: 10.1136/gutjnl-2015-309871
|View full text |Cite
|
Sign up to set email alerts
|

TGR5 contributes to glucoregulatory improvements after vertical sleeve gastrectomy in mice

Abstract: Objective Vertical sleeve gastrectomy (VSG) produces high rates of type 2 diabetes remission; however, the mechanisms responsible remain incompletely defined. VSG increases circulating bile acid concentrations and bile acid signalling through TGR5 improves glucose homeostasis. Therefore, we investigated the role of TGR5 signalling in mediating the glucoregulatory benefits of VSG. Design VSG or sham surgery was performed in high-fat-fed male Tgr5+/+ (wild type) and Tgr5−/− (knockout) littermates. Sham-operate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
193
2
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(213 citation statements)
references
References 39 publications
16
193
2
2
Order By: Relevance
“…Similarly, McGavigan et al 14 generated an independent TGR5 knockout mouse line and obtained results that were consistent with Ding’s observations that VSG improved fasting glycemia, glucose tolerance, and glucose-stimulated insulin secretion. VSG also produced favorable shifts in gut microbial populations in both genotypes.…”
Section: Are Bile Acid Receptors Fxr and Tgr5 The Molecular Targetsupporting
confidence: 70%
See 1 more Smart Citation
“…Similarly, McGavigan et al 14 generated an independent TGR5 knockout mouse line and obtained results that were consistent with Ding’s observations that VSG improved fasting glycemia, glucose tolerance, and glucose-stimulated insulin secretion. VSG also produced favorable shifts in gut microbial populations in both genotypes.…”
Section: Are Bile Acid Receptors Fxr and Tgr5 The Molecular Targetsupporting
confidence: 70%
“…That study, backed up by Dr. Ding’s study, suggests that TGR5 is a molecular target of bariatric surgery. 14 However, it remains unclear which VSG-generated signals activate TGR5 and the specific downstream effectors of postoperative TGR5 activation.…”
Section: Are Bile Acid Receptors Fxr and Tgr5 The Molecular Targetmentioning
confidence: 99%
“…We have also shown that FXR is an important contributor to the weight loss and improved glucose metabolism after bariatric surgery in mice (Ryan et al, 2014). In contrast, experiments with Tgr5-deficient mice showed that TGR5 did not contribute to the reduced body weight, increased energy expenditure, or increased glucose-stimulated insulin secretion after vertical sleeve gastrectomy (VSG) (McGavigan et al, 2015). However, glucose tolerance, hepatic insulin signaling, and metabolically favorable changes in bile acid profiles after VSG were attenuated in the Tgr5-deficient mice, indicating that TGR5 has an impact on at least some of the beneficial effects after bariatric surgery.…”
Section: Changes In Microbiota-bile Acid Interactions After Bariatricmentioning
confidence: 88%
“…Whole-body deletion of FXR results in mice that gain less weight on a HFD but nevertheless have reduced responses to VSG for long-term weight loss, reductions in food intake, and improvements in glucose tolerance (Ryan et al, 2014). Mice with no TGR5 signaling have normal body weight loss following VSG, but have less improvements in glucose regulation (McGavigan et al, 2017). The point is that molecular targeting of bile acid signaling provides evidence that alterations in bile acids are an important physiological mechanism by which surgical intervention can alter energy balance and metabolism.…”
Section: Bariatric Surgeries: Toward Understanding Gut-brain Signalinmentioning
confidence: 99%